2019
DOI: 10.1002/ece3.5397
|View full text |Cite
|
Sign up to set email alerts
|

Does past evolutionary history under different mating regimes influence the demographic dynamics of interspecific competition?

Abstract: Interspecific interactions are contingent upon organism phenotypes, and thus phenotypic evolution can modify interspecific interactions and affect ecological dynamics. Recent studies have suggested that male–male competition within a species selects for capability to reproductively interfere with a closely related species. Here, we examine the effect of past evolutionary history under different mating regimes on the demographic dynamics of interspecific competition in Callosobruchus seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…A mate choice experiment showed that males from polyandrous populations had a higher probability of mating than those from monogamous populations 93 , potentially due to having evolved under strong male-male competition and hence initiating courtship faster and more frequently than monogamous males 94 . Similarly, an experimental evolution study on a seed beetle, Callosobruchus chinensis , also showed that beetles evolved under a polygamous regime caused stronger reproductive interference on the congener, C. maculatus , than beetles evolved under a monogamous regime 95 , 96 . In addition to the above examples, multiple empirical studies have proposed a role of sexual selection in occurrence of reproductive interference between species 97 , 98 .…”
Section: Discussionmentioning
confidence: 94%
“…A mate choice experiment showed that males from polyandrous populations had a higher probability of mating than those from monogamous populations 93 , potentially due to having evolved under strong male-male competition and hence initiating courtship faster and more frequently than monogamous males 94 . Similarly, an experimental evolution study on a seed beetle, Callosobruchus chinensis , also showed that beetles evolved under a polygamous regime caused stronger reproductive interference on the congener, C. maculatus , than beetles evolved under a monogamous regime 95 , 96 . In addition to the above examples, multiple empirical studies have proposed a role of sexual selection in occurrence of reproductive interference between species 97 , 98 .…”
Section: Discussionmentioning
confidence: 94%
“…Competition outcomes are not always consistent across studies. Although the typical outcome is the extinction of C. maculatus (as was the case in Kishi et al, 2009), some studies have shown the extinction of C. chinensis (Fujii, 1969;Ishii & Shimada, 2008;Kyogoku et al, 2019;Utida, 1953). Kawatsu and Kishi (2018) reanalyzed the results of Kishi et al (2009) and Ishii and Shimada (2008) using a time series analysis technique and found evidence for the action of stronger reproductive interference in the experiment of Kishi et al (2009) than that of Ishii and Shimada (2008).…”
Section: Population-level Consequencesmentioning
confidence: 99%
“…In a typical laboratory setting where adults are not provided food or water, resource competition is limited to the larval stage, whereas reproductive interference is limited to the adult stage. This life‐stage specific occurrence of competitive interactions allowed several studies to examine the relative importance of the two modes of species interactions (Kawatsu & Kishi, 2018; Kishi et al, 2009; Kyogoku et al, 2019).…”
Section: Interspecific Interactionsmentioning
confidence: 99%
See 2 more Smart Citations